APPLICATION OF DIGITAL TECHNOLOGIES IN THE PROCESS OF PRODUCTION MANAGEMENT IN TEXTILE ENTERPRISES (Marketing Journal, 2026)
The study systematically examined the theoretical foundations of integrating digital technologies into the production management process of textile enterprises . Within the Industry 4.0 paradigm , the functional role of IoT, ERP, artificial intelligence , and Digital Twin technologies in enhancing production efficiency was analyzed . Based on a systematic review of scientific literature and analytical reports published worldwide , the mechanisms of digital transformationʼs impact on textile manufacturing were identified . The effectiveness of digital technologies in quality control , resource optimization , and supply chain management was substantiated through empirical evidence . The main barriers to implementation - financial constraints , shortage of qualified personnel , and insufficient technological infrastructure - were identified . The research results established a theoretical basis for developing a phased strategy for implementing digital technologies in textile enterprises .
Keywords: digital technologies; textile industry; production management; Industry 4.0; IoT; ERP; artificial intelligence; digital twin; digital transformation